2000
DOI: 10.1038/35004020
|View full text |Cite
|
Sign up to set email alerts
|

p16INK4A and p19ARF act in overlapping pathways in cellular immortalization

Abstract: The INK4A locus encodes two independent but overlapping genes, p16INK4A and p19ARF, and is frequently inactivated in human cancers. The unusual structure of this locus has lead to ambiguity regarding the biological role of each gene. Here we express, in primary mouse embryonic fibroblasts (MEFs), antisense RNA constructs directed specifically towards either p16INK4A or p19 ARF. Such constructs induce extended lifespan in primary MEFs; this lifespan extension is reversed upon subsequent elimination of the p16IN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
225
2
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(242 citation statements)
references
References 31 publications
12
225
2
3
Order By: Relevance
“…Consistently, we have obtained some results showing that p14 ARF is unable to induce a cell cycle arrest in RB-deficient SAOS2 cells and that RB knockdown partially prevents p14 ARF -mediated G 2 arrest in our stable inducible clone (data not shown). These data are reminiscent with a previous study showing that p19 ARF normally functions p14 ARF regulates RB acetylation C Leduc et al by regulating both the RB and p53 pathways (Carnero et al, 2000). In addition, we recently demonstrated that p14 ARF and Tip60 cooperate to induce a p53-independent DNA damage checkpoint in response to alkylating agents (Eymin et al, submitted).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Consistently, we have obtained some results showing that p14 ARF is unable to induce a cell cycle arrest in RB-deficient SAOS2 cells and that RB knockdown partially prevents p14 ARF -mediated G 2 arrest in our stable inducible clone (data not shown). These data are reminiscent with a previous study showing that p19 ARF normally functions p14 ARF regulates RB acetylation C Leduc et al by regulating both the RB and p53 pathways (Carnero et al, 2000). In addition, we recently demonstrated that p14 ARF and Tip60 cooperate to induce a p53-independent DNA damage checkpoint in response to alkylating agents (Eymin et al, submitted).…”
Section: Discussionsupporting
confidence: 84%
“…Collectively, these observations demonstrate that p14 ARF interferes in a direct or indirect manner with some effectors of the RB signalling pathway to control cell growth. The importance of such relationships is underlined by the fact that in a genetic study in mice, p14 ARF has been reported to functionally activate both the p53 and the RB pathways (Carnero et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…More than half of human cancer types present mutations in the TP53 gene (Hollstein et al, 1991), probably because its normal activity would hamper the accumulation of genetic lesions needed for malignant progression (Campbell et al, 2010). Albeit TP53 knockout suffices to immortalize mouse cells (Carnero et al, 2000), no similar outcome has been observed in human cells unless they constitutively express telomerase, possibly owing to the shortness of human telomeres, which limits their lifespan (Hahn and Weinberg, 2002). Nonetheless, it is possible to immortalize primary human prostate epithelial cells by ectopic expression of c-MYC , an oncogene overexpressed in approximately 30% of human cancers (Dang et al, 2008).…”
Section: Early Steps In Carcinogenesis and Metabolismmentioning
confidence: 99%
“…In the absence of p53, Arf still exerts its tumor suppressor function through mechanisms implying other regulators (Carnero et al, 2000;Weber et al, 2000). In this context, p14 ARF has been shown to interact with E2F1 and inhibits its transcriptional activity (Eymin et al, 2001).…”
Section: Introductionmentioning
confidence: 99%